Analysis Influence Factors Negotiation Model, Competency and Domination of Stakeholders to Project Success in Indonesia - Ladika Ladika; Johan Budiman (Enrichment : Journal of Management, 2022)
Construction projects play an important role in the advancement of a nation through infrastructure development that leads to economic growth. many factors that influence the success of the project construction, limited to the main variables such as competency of stakeholder , domination of stakeholder and negotiation model. Project success in construction sector must have stakeholders with the competency and domination for knowledge how make the project success. This research based on 100 samples from the infrastructure sector wich which will be analyzed with the partial structural-least square equation model (PLS-SEM). The result of the analysis show that the competency, domination of the Stakeholders and negotiation model giving effect to the project success in partial variable. Simultaneously, competency and domination of stakeholder, project success and characteristic are able to explain about the significant effect upon the business benefit.